Rethinking Islamic Economic and Finance Practices in Indonesia: Some Critical Reviews - Azwar Iskandar; Bayu Taufiq Possumah; Arfan Arifuddin (Faculty of Islamic Economics and Business of UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
This research aimed to review and highlight some issues related to Islamic economic and finance practices in Indonesia. This research used qualitative-descriptive approach with content analysis, library research and critical studies method. This research found some critical points on islamic economic and finance practices in Indonesia, such as (i) islamic banking in Indonesia shows inconsistencies and unwillingly implementation; (ii) the Islamic economics practices not going too far from around financial sector (iii) the practice of islamic finance in indonesia is mostly focused on the Islamic Commercial Finance (ICF) sector and less concerned with Islamic Social Finance (ISF); (iv) shariah financial institutions is more precisely than what is called â€shariah bankâ€ (v) epistemological problems in the islamic economics curriculum need to be answered and resolved to avoid a contraproductive output from its fundamental purposes. It is necessary to conduct re-orientation of sharia banking in order to strengthen the vision of sharia banking. All involving parties should be able to corporate, among them are academics, practitioners, governments, and, moreover, the role of scholars and organizations. It is reorientation and synergy of these parties which shall solve the problem of half-hearted implementation of banking and answer all criticism directed to the sharia banking all this time